A case report of typical well-differentiated papillary mesothelial tumor diagnosed by internal thoracoscopy and literature review - Guo, Jian; Lv, XiaoHui; Zhang, Wei; Dong, Fang; Li, Lei; Liu, Juan; Li, Bing (Frontiers in Oncology, 2024)
We report a case of well differentiated papillary mesothelial tumor (WDPMT) diagnosed by internal thoracoscopic biopsy who has suffered from recurrent pleural effusions for over 35 years together with a history of elevated CA125. We hope to provide a case for the diagnosis of this rare benign and preinvasive pleural tumor, and to recommend the internal thoracoscopy maybe a good choice in these recurrent pleural effusion patients, especially for those minimal lesions not easily detected in CT scan.